Bladder transitional cell carcinoma: a case report - Cabrales Fuentes, José (2025)
In current clinical oncology, transitional cell carcinoma of the bladder serves as a highly representative model for development in basic, pathogenic and therapeutic research. This case report presents a transitional cell carcinoma of the bladder with a diagnostic approach thatintegrates clinical and imaging methods. The patient is a 67-year-old white male with a history of macroscopic hematuria who was referred for diagnostic imaging. A lower abdominal ultrasound revealed a focal exophytic lesion with features suggestive of neoplastic proliferation. Non-contrast and contrast-enhanced computed tomography (CT) scans were performed for staging purposes and to further assess possible secondary infiltration into adjacent organs, including pelvic lymph nodes, and systemic metastases. The study was complemented by cystoscopy, which showed focalmural thickening within the organ, caused by a fluctuating intraluminal lesion with a tumor-like appearance. Surgical resection of the tumor was performed for subsequent histologic examination, which confirmed the diagnosis of low-grade transitional cell carcinoma of the bladder. Therefore, the patient was treated and placed under follow-up. This demonstrates that, provided physicians master fundamentals and procedures, establishing a pathway based on clinical and imaging findings can lead to improved patient care. This article reorients the approach to this nosological entitytoward a relevant and current methodology, grounded in the organized integration of diagnostic studies to be conducted without creating a dichotomy between them.